ANALISIS PENGARUH PENAMBAHAN GEARBOX PADA TURBIN ARCHIMEDES SCREW UNTUK PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) - I Gede Ngurah Arya Raditya; Lie Jasa; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2021)
Utilization of irrigation flows as a source of electrical energy is not too much, because irrigation flows have low head heights so it's hard to do the design and type of power plant used. In addition, the water discharge in the irrigation canal is also a problem because the water seed in the irrigation canal is not always constant which is influenced by seasons and weather factors. In this study, we will discuss the effect of adding a gearbox to the Archimedes screw turbine on the output value of the generator such as electric current, voltage, efficiency, and torque. This micro hydro power plant uses an Archimedes screw turbine which has 9 blades with an angle of 24o and a blade thickness of 0.25 cm. on the gearbox used using a spur gear type which has a total ratio of 4: 9. The results of research conducted on irrigation lines in Munggu Village, Mengwi District, Badung Regency, got the highest rotation results, namely 160.7 rpm at the turbine, 882.4 at gearbox and 1013, 8 rpm on the generator. The highest voltage and current generated by the generator are 11.15 volts and 0.66 amperes. The torque obtained is 0.45 Nm and the highest efficiency is obtained at 0.00638%.